First mitogenome of the family Putoidae (Hemiptera, Coccomorpha) and its phylogenetic implications - Yu-ang Li; Xinyi Zheng; Han Xu; San-an Wu (ZooKeys)
Scale insects are significant pests impacting agriculture, forestry, and ornamental plants. They play a dual role in ecosystems, serving as a food source for insects like bees, producing pigments and wax. Mitochondrial genomes have been widely utilized in phylogenetic studies. However, the mitogenomes of scale insects currently available in GenBank fail to adequately represent the majority of families. In this paper, the first complete mitogenome of Puto sinensis Zheng & Wu, 2025 is described, revealing previously unreported gene rearrangements in scale insects. It has a length of 18,830 bp and a high A+T content of 90.7%. Moreover, the phylogenetic analysis based on mitogenomic sequences shows that archaeococcoids are a paraphyletic group, with the family Putoidae being sister to all neococcoids – a finding consistent with results from nuclear gene and morphological data. This underscores the utility of mitochondrial genome data in reconstructing phylogenetic relationships within the infraorder Coccomorpha.